Digital transformation of public administration at the present stage - G. A. Chmut (Вестник университета)
One of the basic values of the modern state is the orientation of all its services towards meeting people’s needs. Client-centricity was included in the list of 42 initiatives for socio-economic development of Russia until 2030, approved by the Russian Government in 2021. Information-driven interactions between state bodies and the use of up-to-date reliable information published, inter alia, in an open data format will allow to increase the effectiveness of the public administration system. The purpose of the article is to assess the goals, objectives, and basic technologies of the digital transformation of public and municipal administration. In accordance with the purpose identified, the objectives of the study are as follows: to substantiate the need for digital transformation in public administration, identify the strategic direction of such transformation, and reveal its limitations and advantages. The results of the study include an overview and analysis of certain digital services and products used at the federal and regional levels as part of the digital transformation of public administration. The main conclusion of the article is the substantiation of the role that the digital transformation plays in improving the quality of public and municipal services.